Geotechnical analysis and landslide susceptibility of overburden slope material in the Jammu and Kashmir, Western Himalaya - Zahid Habib; Ajay Kumar; Riyaz Ahmad Mir; Irfan Maqbool Bhat; Waseem Qader; Rosan Kumar Mallik (Geosystems and Geoenvironment)
This study examines the geotechnical properties of slope overburden material from Banihal to Ramban road section of National Highway-44 (NH44), Jammu and Kashmir, Western Himalaya. This region consists of Early Palaeozoic rock formations and is prone to mass wasting. Extensive development activities have exacerbated slope instability in this area. For geotechnical analysis, 40 undisturbed soil samples (USS) were collected and assessed for various parameters. Average values indicate moderate natural moisture content (11.6%), liquid limit (32%), plastic limit (24%), and plasticity index (7%), bulk density (1.6 g/cm³), dry density (1.4 g/cm³), cohesion (0.25 kg/cm²), internal friction angle (38°), void ratio (0.8), porosity (0.44%), and specific gravity (2.5%). The observed geotechnical results suggest moderate bearing capacity of the studied slopes, but increased landslide risk due to low cohesion in high moisture conditions. Therefore, these results may act as a policy document, aiding in land-use planning and identifying suitable sites for engineering structures.